Inborn errors of immunity and related microbiome - Hazime, Raja; Eddehbi, Fatima-Ezzohra; El Mojadili, Saad; Lakhouaja, Nadia; Souli, Ikram; Salami, Abdelmouïne; M’Raouni, Bouchra; Brahim, Imane; Oujidi, Mohamed; Guennouni, Morad; Bousfiha, Ahmed Aziz; Admou, Brahim (Frontiers in Immunology, 2022)
Inborn errors of immunity (IEI) are characterized by diverse clinical manifestations that are dominated by atypical, recurrent, chronic, or severe infectious or non-infectious features, including autoimmunity, lymphoproliferative disease, granulomas, and/or malignancy, which contribute substantially to morbidity and mortality. Some data suggest a correlation between clinical manifestations of IEI and altered gut microbiota. Many IEI display microbial dysbiosis resulting from the proliferation of pro-inflammatory bacteria or a decrease in anti-inflammatory bacteria with variations in the composition and function of numerous microbiota. Dysbiosis is considered more established, mainly within common variable immunodeficiency, selective immunoglobulin A deficiency, severe combined immunodeficiency diseases, Wiskott–Aldrich syndrome, Hyper-IgE syndrome, autoimmune polyendocrinopathy–candidiasis–ectodermal-dystrophy (APECED), immune dysregulation, polyendocrinopathy, enteropathy X-linked (IPEX) syndrome, IL-10 receptor deficiency, chronic granulomatous disease, and Kostmann disease. For certain IEIs, the specific predominance of gastrointestinal, respiratory, and cutaneous involvement, which is frequently associated with dysbiosis, justifies the interest for microbiome identification. With the better understanding of the relationship between gut microbiota, host immunity, and infectious diseases, the integration of microbiota modulation as a therapeutic approach or a preventive measure of infection becomes increasingly relevant. Thus, a promising strategy is to develop optimized prebiotics, probiotics, postbiotics, and fecal microbial transplantation to rebalance the intestinal microbiota and thereby attenuate the disease activity of many IEIs.